Review of the economic evaluations of hormonal therapy for patients with locally advanced prostate cancer. (April 2013) - Hatoum, Hind T; Crawford, E David; Nielsen, Sandy Kildegaard; Lin, Swu-Jane; Marshall, Dennis C
Androgen deprivation therapy (ADT) is used as first-line therapy for locally advanced or metastatic prostate cancer aiming to reduce testosterone to castrate levels. The authors present an overview of the existing cost–effectiveness studies of ADT in prostate cancer. Cost–effectiveness of ADT was reviewed using a systematic search of the peer-reviewed literature, as well as research abstracts presented at various scientific and industry meetings. Most cost–effectiveness analyses of ADT reported results within the accepted societal threshold of US50, 000 cost/quality-adjusted life year needed to adopt new technology.